2009
DOI: 10.1093/aje/kwp268
|View full text |Cite
|
Sign up to set email alerts
|

Body Size, Recreational Physical Activity, and B-Cell Non-Hodgkin Lymphoma Risk Among Women in the California Teachers Study

Abstract: Nutritional status and physical activity are known to alter immune function, which may be relevant to lymphomagenesis. The authors examined body size measurements and recreational physical activity in relation to risk of B-cell non-Hodgkin lymphoma (NHL) in the prospective California Teachers Study. Between 1995 and 2007, 574 women were diagnosed with incident B-cell NHL among 121,216 eligible women aged 22-84 years at cohort entry. Multivariable-adjusted relative risks and 95% confidence intervals were estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
68
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(82 citation statements)
references
References 51 publications
13
68
1
Order By: Relevance
“…Table 1 presents the main characteristics and results of the 15 cohort studies (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) and eight case-control studies (18)(19)(20)(21)(22)(23)(24)(25) included. Three studies investigated more than one physical activity domain (19,24,40) and nine studies provided results stratified by gender (20,22,23,25,26,29,32,39,40).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 presents the main characteristics and results of the 15 cohort studies (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) and eight case-control studies (18)(19)(20)(21)(22)(23)(24)(25) included. Three studies investigated more than one physical activity domain (19,24,40) and nine studies provided results stratified by gender (20,22,23,25,26,29,32,39,40).…”
Section: Resultsmentioning
confidence: 99%
“…If risk estimates were provided for different numbers of adjustment factors, the maximally adjusted risk estimate was used. If a study presented several risk estimates for physical activity at various time periods in life, the risk estimate for the most recent time period was chosen (21,22,34) as most studies provided risk estimates for recent physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas height is determined by genetic as well as environmental factors, such as nutritional status during childhood and adolescence, weight and BMI reflect nutritional status during adulthood as well. A number of case-control and cohort studies have evaluated associations between these anthropometric factors and risk of lymphoid neoplasms in Western populations (5)(6)(7)(8)(9)(10)(11)(12). Although several of these showed a positive association between height and lymphoid neoplasm risk (5-9), others did not (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Only one previous study has examined lifetime non-occupational physical activity in relation to NHL risk, with the results indicating no association (14). In regard to physical activity intensity, although it is possible that vigorous-intensity physical activity is required to reduce NHL risk, another explanation is that measures of vigorous-intensity physical activity are better able to distinguish between active and inactive participants.…”
Section: Discussionmentioning
confidence: 99%
“…Although two studies have found that physical activity may have a greater influence on follicular lymphoma risk than diffuse large B-cell lymphoma risk (17,18), most studies have found little variation between physical activity and the risk of different NHL subtypes (14,16,(19)(20)(21)(22)(23). It remains unclear whether the association between physical activity and NHL risk varies by subtype.…”
Section: Discussionmentioning
confidence: 99%